Chronic renal disease in pregnancy: obstetric outcomes and effect of pregnancy on renal function. (7th June 2011) - Bonnett, T J; Khalid, A; Throssell, D; Farrell, T; Jokhi, R P
Abstract : Introduction: Chronic renal impairment is associated with adverse obstetric outcomes including pre-eclampsia, prematurity and intra-uterine growth restriction. Pregnancy can accelerate decline in renal function: degree of deterioration is dependent on pre-pregnancy renal function, underlying diagnosis and association with chronic hypertension and proteinuria. Methods: This retrospective longitudinal cohort study investigated obstetric outcomes and pregnancy-related changes in renal function in patients attending a tertiary renal antenatal clinic over a 5 year period. Details of renal function pre-pregnancy, during each trimester and postpregnancy were collected via the Proton renal database. Obstetric outcome data was collected via Protos Maternity System and included gestation at delivery and customised birthweight centiles. Results: 75 patients with a wide range of renal diagnoses were included in the study, including four renal transplant patients. Mean delivery gestation was 36+6 weeks. Mean birthweight was 2727 g: mean customised birthweight centile was 32. There were 73 livebirths and 2 terminations of pregnancy with no stillbirths or neonatal deaths. Mean pre-pregnancy creatinine was 93 µmol/l and eGFR 63. Mean postpregnancy creatinine was 131 µmol/l and eGFR 55. 14% patients had a significant decline in postpregnancy renal function. All patients with a booking creatinine >100 µmol/l delivered infants with a birthweight centile of <30. The four renal transplant patients demonstrated no significant difference between pre- and postpregnancy renal function. Conclusion: This study demonstrates favourable pregnancy outcomes in patients with chronic renal disease. Higher creatinine levels at booking correlated with lower birthweight. Most patients in this cohort avoided a significant decline in postpregnancy renal function.